Pengaruh Strategi Promosi dan Kualitas Pelayanan terhadap Minat Transaksi Nasabah yang Dimediasi oleh Kepuasan Nasabah pada Hana Bank Kantor Cabang Jakarta Selatan - Setiawan, Stephen William (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the effect of promotion strategy and service quality on customer transaction interest at Hana Bank, South Jakarta Branch, with customer satisfaction as a mediating variable. The research addresses the inconsistency found in previous studies regarding the role of satisfaction as a mediator in influencing customer behavior. Using a quantitative approach, the study surveyed 160 Hana Bank customers selected through probability sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The findings reveal that promotion strategy and service quality have a positive and significant effect on customer satisfaction. Both variables also directly and positively influence customer transaction interest. Furthermore, customer satisfaction significantly mediates the relationship between promotion strategy, service quality, and transaction interest. These results highlight the strategic importance of effective promotional efforts and high-quality service in enhancing customer satisfaction and encouraging transactional behavior in the banking industry.